Keterlaksanaan Program Praktik Industri Program Keahlian Teknik Pemesinan Di SMK Muhammadiyah 1 Kepanjen Menggunakan Evaluasi Model Kirkpatrick - Ahmad Iqbal Ismawanto (Universitas Negeri Malang, 2020)
Abstract: This study aims to observe the implementation of industrial training program using Kirkpatrick evaluation model which focuses on the human source development. This study utilizes the Kirkpatrick four-level training evaluation model consisting of reaction, learning, behaviour, and result. The subjects of this study are students of mechanical engineering program and a few of industrial training tutors in SMK Muhammadiyah 1 Kepanjen. This study used questionnaires, tests, and documentations as the instruments. The results shows that in the reaction level, the level of performance of the trained students using indicators such as facilities, material, instructors, time, and infrastructure are within the good category. The results of pre-test and post-test of the learning aspects—with the mean value of 61,83 and mean value of 80,83—show that there is significant change to the performance. From behaviour level, referring to tutor assessments using indicators such as communication proficiency, intellectuality, cognitive and motoric strategy, as well as student behaviours are also within the good category. Result shows mean value of 83,7 (> Minimum Criteria of Mastery Learning 75) thus resulting in good category. Keywords: Evaluation, Industrial Training, Kirkpatrick, Program Implementation, SMK